Modal Analysis of Vehicle Power Trains. Issue 1 (21st October 2015) - Haslinger, Josef; Offner, Günter; Sopouch, Martin; Zinkiewicz, Bianka
Abstract In this study, modal analysis of vehicle power trains is based on the linearization of the underlying equations of motions at specified time instants. The equations of motion represent a flexible multi‐body system where force‐elements (joints) connect different bodies. Whenever the linearization leads to an ordinary differential equation with constant coefficients, a standard eigenvalue procedure is used, to compute eigenvalues and mode shapes. The concept is applied to a vehicle power train. Comparison of the results with a commercial software product provide good agreement. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)